دور المرافقة في تحفيز الروح المقاولاتية بالجامعة الجزائرية تقييم الواقع - لوارتي، إبراهيم (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدارسة إلى استكشاف الدور الذي تلعبه المرافقة في تشجيع روح المقاولاتية بين خريجي الجامعات، الذين أصبحوا الآن أكثر ميلاً لخلق فرص عمل بدلًا من البحث عنها، ويتحقق ذلك من خلال دمج ثقافة المقاولاتية بالبرامج والأنشطة المرافقة التي تمنكهم من اكتساب مهارات جديدة مع تعزيز روح المبادرة والمخاطرة التي تجسدها روح المقاولاتية، والتي يتم تشجيعها وتثمينها من قبل أقسام الجامعة كدار المقاولاتية، وخلصت الدراسة إلى أن دار المقاولاتية من خلال المرافقة والتوعية تساهم في تفعيل وتعزيز روح المقاولاتية لدى الطلاب كما أنها تساعدهم على إقتحام قطاع الأعمال من خلال توفير دورات تدريبية، وإرشادات تجارية، وبيئة تنظيمية مناسبة ــ بشرياً ومادياً ــ تدعم إنجاز مشاريعهم واستدامتها. وعلى العكس من ذلك، فإن ضعف روح المقاولاتية بين الطلاب ينجم عن الافتقار إلى المرافقة وأنظمة الدعم المختلفة أو عدم كفايتها، وهو ما يؤثر سلباً على توجههم نحو المقاولاتية. This study aims to explore the role that accompaniment plays in encouraging the entrepreneurial spirit among university graduates, who are now more inclined to create job opportunities instead of searching for them, and this is achieved by integrating the culture of entrepreneurship with accompanying programmes and activities that enable them to acquire new skills while promoting the spirit of initiative and risk-taking that is embodied by the entrepreneurial spirit, which is encouraged and valued by university departments such as the Contracting House. The study concluded that the Entrepreneurship House, through accompaniment and awareness-raising, contributes to activating and enhancing the entrepreneurial spirit among students and helps them to enter the business sector by providing training courses, business guidance, and a suitable organizational environment - human and material - that supports the completion and sustainability of their projects. Conversely, weak entrepreneurial spirit amongstudents results from a lack of or inadequateaccompaniment and support systems, which negatively affects their entrepreneurial orientation.
The role of accompaniment in stimulating the entrepreneurial spirit in Algerian universities: Assessment of reality
Keywords: مرافقة; مقاولاتية; دار المقاولاتية; Accompaniment; Entrepreneurship; Entrepreneurship House